Produção e teores de nutrientes no capim braquiária adubado com nitrogênio e enxofre - Heinrichs, Reges [UNESP]; Grano, Fernanda Grecco [UNESP]; Bueno, Leda Gobbo de Freitas [UNESP]; Soares Filho, Cecilio Viega [UNESP]; Fagundes, Jailson Lara; Rebonatti, Melina Daniel [UNESP]; de Oliveira, Katia [UNESP] (FapUNIFESP (SciELO), 2013)
Among the production factors, adequate fertilization is an important tool to raise the productivity of pastoral systems and consequently increase the share of Brazil in the supply chain of primary agricultural products at the global level. The objective of this study was to evaluate the interaction of nitrogen and sulfur fertilization in Brachiaria decumbens Stapf. The experiment in pots with Dystrophic Oxisol was evaluated in a completely randomized design with four replications in a 5 x 3 factorial arrangement, involving five N doses (0, 100, 200, 400, and 800 mg dm-3) in the form of ammonium nitrate and three S doses (0, 20 and 80 mg dm-3) in the form of calcium sulfate, with a total of 15 treatments. In the treatments with low S dose, calcium was provided as calcium chloride, to ensure a homogeneous Ca supply in all treatments. The results showed that the tiller production and dry weight of green leaves and of stems + sheaths and total dry weight were favored by the combination of N and S fertilizer, while the proportion of dry leaves was reduced. Nitrogen fertilization raised the N contents in green leaves and stems + sheaths and reduced K contents in fresh and dry leaves. The response to S rates in the N content of green leaves was quadratic.
Brachiaria sp yield and nutrient contents after nitrogen and sulphur fertilization
Keywords: Brachiaria decumbens; Fertilization; Forage plants; Plant nutrition